Nilai Budaya Bali dalam Film A Perfect Fit (Studi Semiotika Roland Barthes) - Syifa Fauziah Anwar; Amanda Putri Rahayu; Trie Utari Dewi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Matters related to human reason and mind can be understood as a culture. Every culture has different values. Film is one of the media that can be used to introduce culture. This study aims to determine the Balinese cultural values contained in the film a Perfect Fit directed by Hadrah Daeng Ratu. The researcher uses descriptive qualitative method, with Roland Barthes' semiotic study which explains the idea of significance seen through two stages, namely connotation and denotation. The results obtained from this study are the Balinese cultural values contained in the film a Perfect Fit, among others, namely: (1) Canang Sari is a form of offering (2) Mepantigan is a martial art as an expression of gratitude and mutual trust between group members or society ( 3) Melukat is a ceremony or procession of self-cleaning to avoid negative aura (4) Kecak dance has a meaning to remind the whole community to always think before acting (5) Reading Weton is a procession to match the date of birth to determine the auspicious day of marriage (6) Bebayuhan ceremony called bebayuhan is a process of getting rid of negative things that are brought from birth (7) Balinese Wedding Traditional Dress means that a pair of humans are mentally and physically ready to build a household.